2012
DOI: 10.1016/j.febslet.2012.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Near‐cognate suppression of amber, opal and quadruplet codons competes with aminoacyl‐tRNAPyl for genetic code expansion

Abstract: Over 300 amino acids are found in proteins in nature, yet typically only 20 are genetically encoded. Reassigning stop codons and use of quadruplet codons emerged as the main avenues for genetically encoding non-canonical amino acids (NCAAs). Canonical aminoacyl-tRNAs with near-cognate anticodons also read these codons to some extent. This background suppression leads to ‘statistical protein’ that contains some natural amino acid(s) at a site intended for NCAA. We characterize near-cognate suppression of amber,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 54 publications
(83 reference statements)
8
80
1
Order By: Relevance
“…It was recently reported that the E. coli tRNACUUArg could efficiently suppress an AGGA codon at position 134 of a sequence-optimized sfGFP variant. 24 However, we did not detect the signal (27752.1 Da) corresponding to the Arg incorporation in GFP UV -149AGGA (Supplementary Figure 3 and 4). Since we also did not detect obvious natural amino acid incorporation in response to AGGA codons in chloramphenicol acetyltransferase (position 98, for positive selection) and in barnase (positions 2 and 44, for negative assays; Supplementary Figure 5) for both wt and mutant tRNAUCCUPyl in our experiments, we hypothesized that the previous reported suppression of AGGA codon by E. coli tRNACUUArg might be specific to the codon (position 134) context in sfGFP.…”
Section: Resultsmentioning
confidence: 74%
“…It was recently reported that the E. coli tRNACUUArg could efficiently suppress an AGGA codon at position 134 of a sequence-optimized sfGFP variant. 24 However, we did not detect the signal (27752.1 Da) corresponding to the Arg incorporation in GFP UV -149AGGA (Supplementary Figure 3 and 4). Since we also did not detect obvious natural amino acid incorporation in response to AGGA codons in chloramphenicol acetyltransferase (position 98, for positive selection) and in barnase (positions 2 and 44, for negative assays; Supplementary Figure 5) for both wt and mutant tRNAUCCUPyl in our experiments, we hypothesized that the previous reported suppression of AGGA codon by E. coli tRNACUUArg might be specific to the codon (position 134) context in sfGFP.…”
Section: Resultsmentioning
confidence: 74%
“…In vitro aminoacylation and in vivo UGA translation assays were performed as previously described (25). Experimental details are in SI Experimental Procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the wild type β-galactosidase (Met3), endogenous Trp-tRNA Trp significantly suppresses the stop codon function of UGA, leading to 15 ± 2% translational read-although of UGA (Fig. 5A) (25). Expression of SR1 tRNA Gly UCA leads to enhanced read-through of UGA (22 ± 2%), and expression of the SR1 GlyRS yields additional UGA translation (25 ± 3%).…”
Section: Sr1 Glyrs and Trnamentioning
confidence: 98%
“…6 By simply mutating the anticodon of tRNA Pyl , we showed that the pair could be successfully reprogrammed to reassign opal and ochre codons for coding ncAAs such as N ε -(t-butyloxycarbonyl)-lysine (BocK), N ε -(allyloxycarbonyl)-lysine (AllocK), and N ε -(t-propargyloxycarbonyl)-lysine (ProK) (Scheme 1). 5 However, when we attempted to use the same strategy to reassign a four-base AGGA codon at the 134 th amino acid site of a sequence-optimized superfolder green fluorescent protein (sfGFP) gene, a full-length protein with Arg134 was predominantly produced, indicating strong frameshift suppression from endogenous arginyl-tRNA Arg .…”
mentioning
confidence: 99%
“…The presence of 5 mM BocK in the growth medium did not lead to a significant level of BocK incorporation at the AGGA codon site. 6c However, when a different GFP strain, GFP UV with no sequence optimization and an AGGA mutation at its 149 th amino acid site was used for a similar test, GFP UV with BocK149 was successfully produced in cells that expressed the PylRS-tRNAnormalUnormalCnormalCnormalUPyl pair and were grown in the presence of BocK (Figure 1A). The molecular weight of the purified protein determined by electrospray ionization mass spectrometry (ESI-MS) agreed well with its theoretical value (Figure 1B).…”
mentioning
confidence: 99%